2001
DOI: 10.1105/tpc.13.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Petunia Ap2-like Genes and Their Role in Flower and Seed Development

Abstract: We have isolated three Apetala2 ( Ap2 )-like genes from petunia and studied their expression patterns by in situ hybridization. PhAp2A has a high sequence similarity to the A function gene Ap2 from Arabidopsis and a similar expression pattern during flower development, suggesting that they are cognate orthologs. PhAp2B and PhAp2C encode for AP2-like proteins that belong to a different subgroup of the AP2 family of transcription factors and exhibit divergent, nearly complementary expression patterns during flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…PtAP2L2 is expressed in both female and male cones. In contrast, IDS1 and PhAp2B are expressed much more strongly in stamens rather than in carpels, where little or no expression is observed (Chuck et al 1998;Maes et al 2001).…”
Section: Expression Patterns Of Two-ap2-domain-containing Genesmentioning
confidence: 62%
See 3 more Smart Citations
“…PtAP2L2 is expressed in both female and male cones. In contrast, IDS1 and PhAp2B are expressed much more strongly in stamens rather than in carpels, where little or no expression is observed (Chuck et al 1998;Maes et al 2001).…”
Section: Expression Patterns Of Two-ap2-domain-containing Genesmentioning
confidence: 62%
“…The resulting gene tree showed that the AP2 subfamily consists of ANT homologous genes and AP2 homologous genes, and that PtANTL1 clusters with ANT with moderately high bootstrap values. PtAP2L1 also clusters with A. thaliana AP2 (Jofuku et al 1994) and NP 201519, P. hybrida PhAp2A (Maes et al 2001), Malus domestica AHAP2, Pisum sativum AAK14326, and Picea abies PaAP2L1 (Vahala et al 2001), with moderately high bootstrap values. In contrast, the phylogenetic relationship between PtAP2L2 and the other AP2 homologous genes was unclear, and could not be clarified by a gene tree constructed with only AP2 homologous genes (data not shown).…”
Section: Gene Tree Of Two-ap2-domain-containing Genesmentioning
confidence: 89%
See 2 more Smart Citations
“…Martin and Gerats 1993;Colombo et al 1997;Mol et al 1998;Robbins et al 2000). Over the past decade both forward Van den Broeck et al 1998) and reverse Maes et al 1999Maes et al , 2001 genetic approaches have been developed and applied successfully to recover mutant alleles and characterise mutant phenotypes in petunia.…”
Section: Introductionmentioning
confidence: 99%